Government Expenditure and Its Role Against North Maluku Economic Growth - Runtunuwu, Prince Charles Heston; Topa, Awalluddin; Hasyim, Azis (Jurnal Ekonomi Manajemen Akuntansi Keuangan Bisnis Digital, 2023)
The purpose of this study is to analyze the effect of personnel spending, capital spending, goods and services spending on economic growth in North Maluku. Then also analyze the effect of economic growth on welfare in North Maluku. The method of data analysis is using time series data for 2010-2015 and using multiple linear regression analysis . The results found that based on the results of this study indicate that local government personnel spending has a significant effect and is positively correlated to the economic growth of North Maluku Province. This means that, if there is an increase in spending on government personnel, it will encourage an increase in the regional economy. Furthermore, also that government spending has a positive and significant effect on economic growth in North Maluku Province. This means that, if there is an increase in government capital spending, it will be able to increase economic growth in North Maluku Province. Then also the results of the study show that spending on goods and services has a significant effect and is positively correlated to economic growth in North Maluku Province. This means that, increasing spending on goods and services will be able to boost economic growth.